Keefektifan Teknik Membaca Cepat dalam Bahasa Arab di Pondok Pesantren Darut Tauhid Patemon Krejengan Probolinggo - Adinda Atiqotuz Zummah; Ainur Rofiq Sofa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study discusses the effectiveness of speed reading techniques in learning Arabic at the Darut Tauhid Patemon Islamic Boarding School. Speed ​​reading skills are very important for students to understand Arabic texts, such as classical books and other Islamic literature, in a shorter time. This study uses a qualitative method with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that the speed reading techniques applied in this Islamic boarding school are divided into three levels: beginner, intermediate, and advanced. The technique for beginners emphasizes the introduction of letters and harakat, mastery of understanding using the flashcard method, and repeated reading exercises using the shadowing method. At the intermediate level, students are trained to use skimming and scanning techniques, reading in phrases using the eye movement control method, and understanding the context of the text. Meanwhile, the advanced level focuses on evaluating understanding, discussion, and oral speed reading tests. Although this technique has proven effective in improving reading skills, there are several obstacles, such as limited understanding of students and lack of intensive practice outside of formal class hours. Therefore, a more optimal mentoring strategy is needed, such as increasing comprehension exercises, using technology in learning, and additional training for students who experience difficulties. With proper application, speed reading techniques can improve students' competence in understanding the texts they have mastered.